Epstein Barr Virus: Development of Vaccines and Immune Cell Therapy for EBV-Associated Diseases - Cui, Xinle; Snapper, Clifford M. (Frontiers in Immunology, 2021)
Epstein-Bar virus (EBV) is the first human tumor virus discovered, and is strongly implicated in the etiology of multiple lymphoid and epithelial cancers. Each year EBV associated cancers account for over 200,000 new cases of cancer, and cause 150,000 deaths world-wide. EBV is also the primary cause of infectious mononucleosis, and up to 70% of adolescents and young adults in developed countries suffer from infectious mononucleosis. In addition, EBV has been shown to play a critical role in the pathogenesis of multiple sclerosis. An EBV prophylactic vaccine that induces neutralizing antibodies holds great promise for prevention of EBV associated diseases. EBV envelope proteins including gH/gL, gB and gp350 play key roles in EBV entry and infection of target cells, and neutralizing antibodies elicited by each of these proteins have shown to prevent EBV infection of target cells and markedly decrease EBV titers in the peripheral blood of humanized mice challenged with lethal dose EBV. Recent studies demonstrated that immunization with the combination of gH/gL, gB and/or gp350 induced markedly increased synergistic EBV neutralizing activity compared to immunization with individual proteins. As previous clinical trials focused on gp350 alone was partially successful, the inclusion of gH/gL and gB in a vaccine formulation with gp350 represents a promising approach of EBV prophylactic vaccine development. Therapeutic EBV vaccines have also been tested clinically with encouraging results. Immunization with various vaccine platforms expressing the EBV latent proteins EBNA1, LMP1, and/or LMP2 promoted specific CD4+ and CD8+ cytotoxic responses with anti-tumor activity. The addition of EBV envelope proteins gH/gL, gB and gp350 has the potential to increase the efficacy of a therapeutic EBV vaccine. The immune system plays a critical role in the control of tumors, and immune cell therapy has emerged as a promising treatment of cancers. Adoptive T-cell therapy has been successfully used in the prevention and treatment of post-transplant lymphoproliferative disorder. Chimeric antigen receptor T cell therapy and T cell receptor engineered T cell therapy targeting EBV latent proteins LMP1, LMP2 and/or EBNA1 have been in development, with the goal to increase the specificity and efficacy of treatment of EBV associated cancers.